Innovations in Cancer Therapy: Endogenous Stimuli-Responsive Liposomes as Advanced Nanocarriers - Jazmín Torres; Johanna Karina Valenzuela Oses; Antonio María Rabasco-Álvarez; María Luisa González-Rodríguez; Mónica Cristina García (Pharmaceutics)
Recent advancements in nanotechnology have revolutionized cancer therapy—one of the most pressing global health challenges and a leading cause of death—through the development of liposomes (L), lipid-based nanovesicles known for their biocompatibility and ability to encapsulate both hydrophilic and lipophilic drugs. More recent innovations have led to the creation of stimuli-responsive L that release their payloads in response to specific endogenous or exogenous triggers. Dual- and multi-responsive L, which react to multiple stimuli, offer even greater precision, improving therapeutic outcomes while reducing systemic toxicity. Additionally, these smart L can adjust their physicochemical properties and morphology to enable site-specific targeting and controlled drug release, enhancing treatment efficacy while minimizing adverse effects. This review explores the latest advancements in endogenous stimuli-responsive liposomal nanocarriers, as well as dual- and multi-responsive L that integrate internal and external triggers, with a focus on their design strategies, mechanisms, and applications in cancer therapy.